Design and Mechanical Evaluation of a Polymer Keel SACH Foot Using Finite Element Analysis and Experimental Validation - Agus Setyo Nugroho; Kazuhiko Sasaki; Muhammad Nouman; Rifky Ismail (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2026)
Conventional Solid Ankle Cushion Heel (SACH) foot commonly uses wooden keels, which may exhibit variability in mechanical properties and limited long-term durability. This study aimed to develop and evaluate a polymer-based keel SACH foot as a low-cost alternative with improved mechanical performance. An integrated methodology combining finite element analysis (FEA) and experimental validation was employed. Three polymer keel SACH foot configurations were designed and analyzed under loading conditions that represent heel strike, mid-stance, and terminal stance, in accordance with ISO 10328. The optimal design was subsequently fabricated and tested under static loading conditions to validate the numerical model. The models utilized ABS for the keel, HDPE for the footplate, and vulcanized rubber for the foot body. Mechanical performance was assessed through total deformation, von Mises stress, strain, and safety factor analysis. Among the three configurations, Model A demonstrated the best mechanical performance, with the lowest average deformation (20.12 mm), the lowest stress concentration (12.67 MPa), and the highest safety factor (1.59). The selected design was subsequently fabricated and validated experimentally under static loading conditions up to 1176.78 N. Experimental validation showed strong agreement with FEA predictions, with deviations below 5% across all gait phases, confirming the accuracy of the FEA model. Comparative testing against a conventional wooden-keel SACH foot revealed significantly lower deformation values for the polymer-based keel SACH foot (p < 0.05), indicating improved structural stiffness and more efficient load distribution during loading process. These findings suggest that replacing conventional wooden keels with polymer-based structures can enhance mechanical consistency and structural reliability, while maintaining manufacturability and cost-effectiveness. The proposed design offers a promising approach to developing an affordable and durable prosthetic foot, particularly for use in low- and middle-income countries